Cooperation of the Police with non-governmental organizations in the field of security and public order - Pieprzny, Stanisław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The article highlights the basic issues related to the cooperation of the Police with non-governmental organizations in the field of security and public order. Such a cooperation results not only from the fact that the Police implement tasks in the aforementioned field, based on the general competence norm, but also that they perform many tasks in the form of non-authoritative activities, typical for social organizations. Both the legal and actual possibilities of cooperation in these entities were indicated and examples of such interaction were highlighted. The role of legal solutions was also emphasized, according to the Act of 24 April 2003 about public benefit activities and voluntary work.

W artykule zasygnalizowane zostały podstawowe zagadnienia związane ze współdziałaniem Policji z organizacjami pozarządowymi w sferze bezpieczeństwa i porządku publicznego. Współdziałanie to wynika nie tylko z faktu, że Policja realizuje zadania w tej sferze w oparciu o ogólną normę kompetencyjną, ale również i z tego, że wiele z zadań wykonuje w formie działań niewładczych typowych dla organizacji społecznych. Wskazano też na prawne i faktyczne możliwości współdziałania tych podmiotów oraz zwrócono uwagę na przykłady tego współdziałania. Podkreślona została rola rozwiązań prawnych zawartych w ustawie z dnia 24 kwietnia 2003 r. o działalności pożytku publicznego i wolontariacie.
Keywords: Police; non-governmental organizations; volunteering; public safety; non-executive functions; cooperation; Policja; organizacje pozarządowe; wolontariat; bezpieczeństwo publiczne; niewładcze formy działania; współdziałanie